Internet and National Identity of Kazakhstan Citizens (Journal of Philosophy Culture and Political Science, 2015)
The article discusses the place of modern information and communication technologies, particularly the Internet, in the life of Kazakhstan society, its impact on national identity of Kazakhstan citizens. The authors conducted an analysis of official statistics on the use of the Internet by population of Kazakhstan, compared them with similar data in the developed countries. On the example of «Arab Spring» authors proved the importance of considering the impact of modern information technologies on social and political stability of the state. The significance of online communities and bloggers, as the main subjects of the virtual space, in the process of socialization of the Kazakh youth was investigated. The position on the possibility of transforming the nation from the «imagined community» to «tangible» community citizens is grounded.
Keywords: Internet; national identity; online communities; nation; «imagined community».